Identification of a novel CD40 ligand for targeted imaging of inflammatory plaques by phage display. Issue 10 (29th July 2013) - Yu, Haixiang; Segers, Filip; Sliedregt‐Bol, Karen; Bot, Ilze; Woltman, Andrea M.; Boross, Peter; Verbeek, Sjef; Overkleeft, Herman; van der Marel, Gijs A.; van Kooten, Cees; van Berkel, Theo J. C.; Biessen, Erik A. L.
Abstract : The CD40/CD40L dyad is deemed to play a central role in several inflammatory processes, including atherosclerosis. As CD40 is overexpressed in atherosclerotic lesions, it constitutes a promising candidate for targeted imaging approaches. Here we describe the design of a novel, selective peptide ligand for CD40 by phage display. A synthetic peptide corresponding with the phage insert NP31 displayed nanomolar affinity for CD40. Affinity was further enhanced by mutimeric presentation of NP31. An essential 11‐mer peptide motif was identified by truncation and alanine scan studies. Enriched phage selectively bound human CD40 and homed to inflammatory joints in a murine model of rheumatoid arthritis. NP31 ablated VEGF and IL‐6 transcriptional activation and partially inhibited IL‐6 production by CD40L‐activated endothelial cells. Notably, NP31 did not only alter the biodistribution profile of a streptavidin scaffold but also markedly increased accumulation of the carrier in atherosclerotic aortic lesions of aged ApoE –/– mice in a CD40‐dependent manner. This potent and selective peptide ligand has potential for targeted imaging and drug delivery approaches in CD40‐dependent inflammatory disorders such as atherosclerosis.—Yu, H., Segers, F., Sliedregt‐Bol, K., Bot, I., Woltman, A. M. Boross, P., Verbeek, S., Overkleeft, H., van der Marel, G. A., van Kooten, C., van Berkel, T J. C., Biessen, E. A. L. Identification of a novel CD40 ligand for targeted imaging of inflammatory plaques by phage display. FASEBJ. 27, 4136‐4146 (2013). www.fasebj.org